Edukasi Manajamen Sampah Berbasis Sumber di Banjar Pohgending, Desa Pitra - Merta Gangga; Dewa Ayu Putu Garini Putri; Putu Indah Dianti Putri (Universitas Serang Raya, 2023)
Garbage is something that is always there in everyday life. All those who are active will definitely produce waste and so is what happened in Pitra Village, Penebel District, Tabanan Regency. In the observations that have been made at the beginning of the Community Service Program, there are several places in the village area that do not yet have a garbage disposal site, so residents often throw garbage out of place. There are also those who throw garbage behind their houses or in certain areas. The accumulated garbage causes unpleasant odors and pollutes the environment. Making trash cans is a solution to provide a facility for residents so that residents can dispose of their garbage in its place. It is hoped that by making this trash can, residents will become accustomed to throwing garbage in its place. Trash cans are familiar things around us, but the existence of trash bins is not necessarily a good thing, even its function cannot be used properly because of the existing waste. it does not match its location or function. By making this trash can, it is hoped that the village can continue to load the trash here to be distributed at every price in the village.